The Relationship Between Acceptable Noise Level and Initial Acceptance of Hearing Aid - Ali Abbasi; Hamid Jalilvand; Leyla Jalilvand Karimi; Alireza Akbarzade Baghban (Negah Institute for Scientific Communication, 2018)
Introduction: The Acceptable Noise Level (ANL) evaluates the willingness of a listener to hear a continuous speech in the presence of background noise. ANL is related to some variables. Although many studies were accomplished on the relationship between ANL and hearing aid satisfaction, no study was found for the usage of ANL as the predictor of initial hearing aid acquisition. Therefore, the current study aimed at determining the relationship between the initial acceptance of hearing aid and individual's ANL. The study also aimed at quantifying human potentials for what is out of their personal control, as well as assessing their commitment in the actions that improve and enrich their quality of life. Methods: A total of 60 patients with hearing loss who were the candidate for wearing hearing aid were participated. ANLs were measured and comprehensive hearing aid counseling was given to the patients. Patients were free to accept or reject using hearing aids. The Pearson correlation was used to assess the relationships among variables, and the independent t test was used to compare data between the groups Results: The analysis revealed a correlation between ANL and the acceptance of hearing aid. ANL means in the subjects who accept and reject hearing aid were 7.83 and 11.73, respectively.  Conclusion: The results showed the correlation between lower ANLs and acceptance of hearing aid and also the correlation between higher ANLs and resistance to get hearing aid. Participants who accepted to take hearing aid had lower ANL mean and the ones who refused to take hearing aid had higher ANL mean.